244. Target volume definition with MRI and 68 Ga-DOTATOC-PET/CT for patients with meningiomas. (December 2018) - Garibaldi, C.; Ferrari, M.; Colandrea, M.; Cascio, A.; Ciocca, M.; Iannalfi, A.; D'Ippolito, E.; Pesente, S.; Grana, C.; Jereczek-Fossa, B.A.; Cremonesi, M.
Abstract: Purpose: To investigate the impact of 68 Ga-DOTATOC PET/CT in addition to MRI and CT for retrospectively assessing the GTV delineation of meningiomas of the skull base in patients treated with particle therapy. Methods: Sixteen patients underwent 68 Ga-DOTATOC PET/CT for diagnosis followed by constract-enhanced (CE) MRI and CT for treatment planning with particle therapy.GTV was defined on the CE-MRI fused to the simulation CT (CTsim ) integrating information from the PET/CT. Three methods to delineate the PET volume were evaluated:manual ( PET man ), semiautomatic (42% threshold of SUV max, PET SUV 42 % ) and automatic adaptive thresholding method incorporating PET reconstruction parameters ( PET auto ) (iTA, TA). PET man volumes were delineated by the same nuclear medicine physician, while PET SUV 42 % and PET auto volumes were determined by medical physicists.The PET/CT, CE-RMI and CT sim were co-registered with a deformable image registration algorithm using the MIM Software.The overlapping region of MRI and PET man resulted in GTV common . Results: The lesions had a median SUV max of 12.1 ± 6.8 (range:3.2–32.6).Overall, the GTV-MRI was larger than GTV-PET man in 7 patients (43.8%), smaller in 6 (37.5%) and almost the same in 3 (18.8%).The median value of the different volumes were:GTV-MRI = 14.3 ± 37.2 cc, GTV-PET man = 14.4 ± 47.0 cc, GTV common = 12.2 ± 33.6 cc, GTV-PET SUV 42 % = 8.3 ± 18.3 cc, GTV- PET auto = 11.3 ± 26.2 cc . GTV-PET SUV 42 % were always smaller than GTV-PET man ( Δ = - 51.0 ± 32.7 % ) and GTV-PET auto ( Δ = - 21.5 ± 12.7 % ) being variations in tumor heterogeneity not accounted for. Largest differences were observed for lesions showing high SD of SUV. The median difference between GTV-PET man and GTV-PET auto was 39.6 ± 29.5%. Conclusions: 68 Ga-DOTATOC-PET/CT seems to improve the target volume delineation in skull base meningiomas, often leading to a reduction of GTV compared with MRI. The automatic adaptive thresholding delineation method may provide robust and reliable tool to help physician in segmenting PET images, reducing inter- and intra-observer variability.